Chlorpyrifos pesticide reduction in soybean using cold plasma and ozone treatments. (1st April 2022) - Anbarasan, R.; Jaspin, S.; Bhavadharini, B.; Pare, Akash; Pandiselvam, R.; Mahendran, R.
Abstract: To meet market demands, soybean is predominantly grown with the excess use of harmful pesticides like chlorpyrifos, which leaves poisonous residues on the seeds' surfaces. In this study, we have treated chlorpyrifos (1, 2 and 3 mg/kg) infused soybean with ozone (300–550 mg/l) and low pressure (2 mbar) cold plasma (CP: 1.0–2.0 kV) for up to a period of 30 min to reduce the pesticide residues. However, it was found that at higher pesticide concentrations, ozone treatment can only cause 50% pesticide reduction after 30 min exposure, even at 550 mg/l concentration. In contrast, CP treatment took only 6 min to achieve the same at 2.0 kV voltage level but caused a significant reduction (P ≤ 0.05) in moisture content and seed coat integrity. However, the water absorption of CP treated samples was higher (∼230%) than ozone-treated samples (∼200%). Furthermore, increased pesticide concentration reduced the pesticide degradation rate for ozone (0.078–0.0643 min −1 ) and cold plasma (0.160–0.143 min −1 ) treatments even at higher treatment intensities. Nevertheless, CP was effective against chlorpyrifos than ozone treatment and caused minor quality changes in soybeans.